1967
DOI: 10.1161/01.cir.36.5.692
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diphenylhydantoin on Left Ventricular Function in Patients with Heart Disease

Abstract: The effect of 250 mg of diphenylhydantoin, administered intravenously, on left ventricular function was determined during cardiac catheterization in nine patients with heart disease. Five minutes after drug administration, left ventricular end-diastolic pressure rose in each patient from an average of 6.0 mm Hg to 10.0 mm Hg. Concurrently, stroke work and stroke power indices decreased in each patient by an average of 22.0% and 22.2%, respectively. Stroke volume index decreased in seven patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1968
1968
1984
1984

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, recently it has been demonstrated that diphenylhydantoin also is not totally devoid of adverse hemodynamic effects since it will depress myocardial function in patients with heart disease. 5 Key: BSA = body surface area in M2; ASHD = arteriosclerotic heart disease; PMD = primary myocardial disease. Time = time in minutes after drug injection with 0 representing the control period; HR = heart rate in beats/min; Mean art pr = mean arterial pressure in mm Hg; CI = cardiac index in L/min/m2; LVEDP = left ventricular end-diastolic pressure in mm Hg; SVI = stroke volume index in mI/M2; SWI = left ventricular stroke work index in g-m/m2; dp/dt = maximum rate of rise of left ventricular pressure as per cent of control.…”
mentioning
confidence: 99%
“…However, recently it has been demonstrated that diphenylhydantoin also is not totally devoid of adverse hemodynamic effects since it will depress myocardial function in patients with heart disease. 5 Key: BSA = body surface area in M2; ASHD = arteriosclerotic heart disease; PMD = primary myocardial disease. Time = time in minutes after drug injection with 0 representing the control period; HR = heart rate in beats/min; Mean art pr = mean arterial pressure in mm Hg; CI = cardiac index in L/min/m2; LVEDP = left ventricular end-diastolic pressure in mm Hg; SVI = stroke volume index in mI/M2; SWI = left ventricular stroke work index in g-m/m2; dp/dt = maximum rate of rise of left ventricular pressure as per cent of control.…”
mentioning
confidence: 99%
“…They noted a direct vasodilating effect on the coronary vessels, with no change in the myocardial consumption of oxygen during a constant work load. Lieberson et al (11) have shown that diphenylhydantoin does not significantly reduce cardiac output or greatly elevate left ventricular end‐diastolic pressure. Thus, improvement in ventricular ectopic activity not related to digitalis may be secondary to an improvement in coronary perfusion and a decrease in ventricular automaticity.…”
Section: Commentmentioning
confidence: 99%
“…Propyl ene glycol, the solvent for DPH, also has cardiotoxic properties (49). DPH is a negative inotropic agent, although the depression of myocardial function appears to be slight and transient (50)(51)(52). It is also a peripheral vasodila tor-producing hypotension, and may cause central nervous system toxicity ataxia, psychoses, and excitability (50).…”
Section: Antiarrhythmic Drugsmentioning
confidence: 99%